2018
DOI: 10.1007/s00246-018-1821-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Increased Aortic Diameters in Young Normotensive Patients With Turner Syndrome Without Structural Heart Disease

Abstract: Factors associated with aortic dilation and dissection in patients with Turner syndrome (TS) remain unclear. We assessed magnetic resonance imaging-based aortic diameters at nine predefined anatomic positions and examined associations of increased aortic diameters with B-type natriuretic peptide (BNP), A-type NP (ANP), growth hormone treatment, insulin-like growth factor 1 (IGF1), and estrogen status. Forty-seven patients with TS aged 7.3-21 years and 34 healthy peers were enrolled in this study. Aortic diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The most common karyotype was 45,X, with other karyotypes including four patients with mosaic 45,X/46,XX, three patients with 46,XiX(q10), one patient each with mosaic 45,X/46,XY and 46,Xdel(X)(p22.1), and one karyotype was unknown. As seen in other cohorts with relatively young Turner syndrome populations (Uçar et al, 2018), treatment with growth hormone was common (78% of the patients). A similar percentage of patients (73%) were treated with estrogen.…”
Section: Resultssupporting
confidence: 63%
“…The most common karyotype was 45,X, with other karyotypes including four patients with mosaic 45,X/46,XX, three patients with 46,XiX(q10), one patient each with mosaic 45,X/46,XY and 46,Xdel(X)(p22.1), and one karyotype was unknown. As seen in other cohorts with relatively young Turner syndrome populations (Uçar et al, 2018), treatment with growth hormone was common (78% of the patients). A similar percentage of patients (73%) were treated with estrogen.…”
Section: Resultssupporting
confidence: 63%
“… 33 , 34 In addition, a recent study on atherosclerosis showed that IGF1 pathway could regulate the inflammation and proliferation of vascular smooth muscle cells. 35 In AD-related disease, IGF1 has been reported to be positively correlated with an increased aortic diameters 36 in Turner syndrome, which is a common cause of AD. NOS3 is a key player in governing angiogenesis, and its aberrant expression will result in the dysfunction of vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%